Legitimizing and De-legitimizing Wars in the News: A Critical Discourse Analysis of the International Coverage of the Ukraine and Gaza War Declarations (المجلة الدولية للعلوم التربوية والآداب, 2026)
This article examines how international media construct the legitimacy of war, focusing on coverage of two conflict declarations: Russia’s invasion of Ukraine and Israel’s military offensive in Gaza. Using a Critical Discourse Analysis framework, the study analyzes reports from The Guardian (UK) and The New York Post (US) to explore how discursive strategies shape public understandings of aggression, victimhood, and moral accountability. Despite a substantial body of research on media coverage of conflicts, comparative studies analyzing discursive strategies across distinct geopolitical contexts remain underrepresented. As such, this study seeks to answer the central research question: how do international media construct and differentiate the legitimacy of war in the context of Russia’s invasion of Ukraine and Israel’s military offensive in Gaza, and what ideological functions are revealed through this comparative analysis? Previous studies have typically focused on single-case analyses, often overlooking how narratives vary across different geopolitical landscapes. This study addresses this gap, revealing clear asymmetries in media coverage: Ukraine is framed through explicit condemnation of Russian aggression, emotive depictions of civilian suffering, and authoritative quotations of Ukrainian and Western leaders. In contrast, Gaza coverage situates Israeli military action within security and counterterrorism narratives, downplays structural context, and marginalizes Palestinian perspectives through selective quotation. This comparative analysis offers unique insights into how the divergent framing of these events reveals broader ideological functions in news discourse, challenging single-case studies by showing how media representations normalize particular narratives of violence across different geopolitical contexts.